A preliminary evaluation of the European Non‐native Species in Aquaculture Risk Assessment Scheme applied to species listed on Annex IV of the EU Alien Species Regulation. (16th May 2014) - Copp, G. H.; Godard, M. J.; Russell, I. C.; Peeler, E. J.; Gherardi, F.; Tricarico, E.; Miossec, L.; Goulletquer, P.; Almeida, D.; Britton, J. R.; Vilizzi, L.; Mumford, J.; et al.
Abstract: Developed for carrying out risk assessments under the European Commission (EC) Council Regulation No 708/2007 concerning the use of alien and locally absent species in aquaculture (ASR), the European Non‐native Species in Aquaculture Risk Assessment Scheme (ENSARS) is briefly summarised, and the 'Organism' module is applied to the 24 species listed in ASR's Annex IV. Four other ENSARS modules (Infectious Agent, Facility, Pathway, and Socio‐economic) were used to assess two case study species (European catfish Silurus glanis L. and red swamp crayfish Procambarus clarkii Girard). No Annex IV species was categorised as low risk, 10 as moderately low risk, 12 as medium risk, two as moderately high risk and none as high risk. The results are discussed and recommendations are made on further development of the scheme as well as the need to have multiple assessors of multidisciplinary expertise from the Member States concerned carry out the assessments using an approach similar to that carried out by EU Reference Laboratory proficiency tests.